AN OVERVIEW OF THE LIFE PHILOSOPHY OF THE SUNDANESE PEOPLE AGAINST THE CULTURAL INTELLIGENCE OF STUDENTS IN EAST PRIANGAN - Nugraha, Agung; Sulistiana, Dewang; Muslim, Ajid (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2021)
The increasing relationship between students with unique and diverse backgrounds as a result of open access through technology needs to be facilitated immediately. The availability of accurate data about the cultural intelligence of students is currently needed so that these students can adapt to their environment and are optimally facilitated. The purpose of this study is to obtain a real picture of the cultural intelligence of students in East Priangan and analyze it from the point of view of the dynamics of individual development and the philosophy of life of the Sundanese ethnic community. This study uses a quantitative approach and uses a descriptive method. Collecting data using a questionnaire to reveal the level of cultural intelligence of students which is then analyzed conceptually and empirically from the point of view of the dynamics of human development. The results showed that the achievement of cultural intelligence of students in East Priangan was above the average. The empirical results indicate that the psychophysical efforts of students to be able to adapt effectively and normatively in a higher education environment are close to optimal. This condition was determined by the real embodiment of the mandates contained in several Sundanese ethnic heritage texts from generation to generation both in thinking, feeling, and behaving.